Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Downregulation of Fidgetin-Like 2 Increases Microglial Function: The Relationship Between Microtubules, Morphology, and Activity - Austin N. Smith; Alison Gregor; Lisa Baker; David J. Sharp; Kimberly R. Byrnes (Molecular Neurobiology, 2025)
The microtubule cytoskeleton regulates microglial morphology, motility, and effector functions. The microtubule-severing enzyme, fidgetin-like 2 (FL2), negatively regulates cell motility and nerve regeneration, making it a promising therapeutic target for central nervous system injury. Microglia perform important functions in response to inflammation and injury, but how FL2 affects microglia is unclear. In this study, we investigated the role of FL2 in microglial morphology and injury responses in vitro. We first determined that the pro-inflammatory stimulus, lipopolysaccharide (LPS), induced a dose- and time-dependent reduction in FL2 expression associated with reduced microglial ramification. We then administered nanoparticle-encapuslated FL2 siRNA to knockdown FL2 and assess microglial functions compared to negative control siRNA and vehicle controls. Time-lapse live-cell microscopy showed that FL2 knockdown increased the velocity of microglial motility. After incubation with fluorescently labeled IgG-opsonized beads, FL2 knockdown increased phagocytosis. Microglia were exposed to low-dose LPS after nanoparticle treatment to model injury-induced cytokine secretion. FL2 knockdown enhanced LPS-induced cytokine secretion of IL-1α, IL-1β, and TNFα. These results identify FL2 as a regulator of microglial morphology and suggest that FL2 can be targeted to increase or accelerate microglial injury responses. Graphical Abstract

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Current Approaches for Dissolution Similarity Assessment, Requirements, and Global Expectations - Andreas M. Abend; Limin Zhang; Emilija Fredro-Kumbaradzi; Thomas Hoffelder; Michael J. Cohen; Om Anand; Poonam Delvadia; Haritha Mandula; Zhen Zhang; Evangelos Kotzagiorgis; Susan Lum; Victor Gomes Pereira; et al. (The AAPS Journal, 2022)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

Aquifer-yield continuum as a guide and typology for science-based groundwater management - Suzanne A. Pierce; John M. Sharp; Joseph H. A. Guillaume; Robert E. Mace; David J. Eaton (Hydrogeology Journal, 2013)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

The Nail as a Noninvasive Indicator of Methylmercury Exposures and Mercury/Selenium Molar Ratios in Brain, Kidney, and Livers of Long-Evans Rats - John Douglas Brockman; Laura Jean Raymond; Carla Rae Ralston; J. David Robertson; Nicole Bodkin; Nicholas Sharp; Nicholas V. C. Ralston (Biological Trace Element Research, 2011)

The molecular basis of anaphase A in animal cells - Uttama Rath; David J. Sharp (Chromosome Research, 2011)

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

Facilitation of extinction of operant behaviour in mice by d-cycloserine - David Shaw; Kelly Norwood; Kim Sharp; Lauren Quigley; Stephen F. J. McGovern; Julian C. Leslie (Psychopharmacology, 2009)

Near‐surface‐temperature lapse rates on the Prince of Wales Icefield, Ellesmere Island, Canada: implications for regional downscaling of temperature - Shawn J. Marshall; Martin J. Sharp; David O. Burgess; Faron S. Anslow (International Journal of Climatology, 2007)
Screen temperatures were monitored from May 2001 to April 2003 in an array of 25 sites on the Prince of Wales Icefield, Ellesmere Island, Canada. The observational network covered an area of ca 15 650 km 2 and spanned an altitude ranging from 130 to 2010 m above sea level. The spatial array provides a record of near‐surface‐temperature lapse rates and mesoscale temperature variability on the icefield. The mean daily lapse rate in the 2‐year record is − 4.1° C km −1 , with an average summer lapse rate of − 4.3° C km −1 . Surface‐temperature lapse rates in the region are therefore systematically less than the free‐air lapse rates that are typically adopted for extrapolations of sea‐level temperature to higher altitudes. Steep lapse rates, resembling moist adiabatic rates in the free air (−6 to − 7° C km −1 ), are more common in summer at our site and are associated with enhanced cyclonic activity (low‐pressure and high relative vorticity) and southerly flow aloft. In contrast, northerly, anticyclonic flow prevails when summer lapse rates are weak (above − 2° C km −1 ). The low surface‐temperature lapse rates and their systematic synoptic variability have important implications for applications that require downscaling or extrapolation of surface‐ or boundary‐layer temperatures, such as modelling of glacier mass balance. We illustrate this in an analysis of observed versus modelled snowmelt on the icefield. Copyright © 2006 Royal Meteorological Society.

Fluxes of semivolatile organochlorine compounds in Bow Lake, a high‐altitude, glacier‐fed, subalpine lake in the Canadian Rocky Mountains - Jules M. Blais; David W. Schindler; Martin Sharp; Eric Braekevelt; Melissa Lafreniěre; Karen McDonald; Derek C. G. Muir; William M. J. Strachan (Limnology and Oceanography, 2001)
The fluxes of several organochlorine compounds (OCs) to and from a high‐altitude lake were calculated to determine the relative contributions of rainfall, snowfall, runoff, gas absorption and volatilization, sedimentation, and outflow. Runoff inputs, particularly from a glaciated catchment, and gas absorption were major sources of many OCs. Losses by volatilization, outflow, and sedimentation were also important transport pathways for most OCs. We observed a net deposition of hexachlorocyclohexanes (HCHs) and DDT to Bow Lake by gas exchange, whereas hexachlorobenzene, chlordanes, and most polychlorinated biphenyls were seen to volatilize to the air. The insecticide lindane (γHCH), widely applied across Canada as a seed dressing in early spring, was absorbed by Bow Lake in early summer but gradually equilibrated with water as the summer progressed. This was the result of lower concentrations of γHCH in air and rising air temperatures in late summer. Results indicate that glacially derived tributary inputs are dominant sources of persistent organic pollutants to these glacier‐fed mountain lakes and that smaller contributions may derive from air‐water gas exchange. This study highlights the importance of glacial sources of OCs to mountain lakes and corroborates recent evidence of OC contamination in glacially derived aquatic systems.

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Accurate scale up of two phase flow using renormalization and nonuniform coarsening - Timothy C. Wallstrom; Shuling Hou; Michael A. Christie; Louis J. Durlofsky; David H. Sharp (Computational Geosciences, 1999)

Xp deletions associated with autism in three females - N. S. Thomas; Andrew J. Sharp; Caroline E. Browne; David Skuse; Chris Hardie; Nicholas R. Dennis (Human Genetics, 1999)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)